Upregulation of the transcription factor TFAP2D is associated with aggressive tumor phenotype in prostate cancer lacking the TMPRSS2:ERG fusion - Christoph Fraune; Luisa Harms; Franziska Büscheck; Doris Höflmayer; Maria Christina Tsourlakis; Till S. Clauditz; Ronald Simon; Katharina Möller; Andreas M. Luebke; Christina Möller-Koop; Stefan Steurer; Claudia Hube-Magg; et al. (BMC, 2020)
Abstract Background TFAP2D is a transcription factor important for modulating gene expression in embryogenesis. Its expression and prognostic role in prostate cancer has not been evaluated. Methods Therefore, a tissue microarray containing 17,747 prostate cancer specimens with associated pathological, clinical, and molecular data was analyzed by immunohistochemistry to assess the role of TFAP2D. Results TFAP2D expression was typically increased in prostate cancer as compared to adjacent non-neoplastic glands. TFAP2D staining was considered negative in 24.3% and positive in 75.7% of 13,545 interpretable cancers. TFAP2D staining was significantly linked to advanced tumor stage, high classical and quantitative Gleason grade, lymph node metastasis, and a positive surgical margin (p ≤ 0.0045). TFAP2D positivity was more common in ERG fusion positive (88.7%) than in ERG negative cancers (66.8%; p < 0.0001). Subset analyses in 3776 cancers with and 4722 cancers without TMPRSS2:ERG fusion revealed that associations with tumor phenotype and patient outcome were largely driven by the subset of ERG negative tumors. Multivariate analysis did not identify TFAP2D protein expression levels as a robust independent prognostic parameter. Positive TFAP2D immunostaining was significantly associated with 10 of 11 previously analyzed chromosomal deletions in ERG negative cancers (p ≤ 0.0244 each) indicating that elevated TFAP2D expression parallels genomic instability in prostate cancer. Conclusion These data demonstrate that TFAP2D protein overexpression is linked to prostate cancer progression and genomic instability in ERG negative prostate cancers.